Mesenchymal stem cell-secreted prostaglandin E2 ameliorates acute liver failure via attenuation of cell death and regulation of macrophage polarization - Jinglin Wang; Yang Liu; Haoran Ding; Xiaolei Shi; Haozhen Ren (Stem Cell Research & Therapy, 2021)
Abstract Background Acute liver failure (ALF) is an acute inflammatory liver disease with high mortality. Previous preclinical and clinical trials have confirmed that mesenchymal stem cell (MSC) is a promising therapeutic approach; however, the effect is not satisfied as the underlying molecular mechanisms of MSC in treating ALF remain unclear. Methods MSC isolated from 4- to 6-week-old C57BL/6 mice were used to treat ALF. Histological and serological parameters were analyzed to evaluate the efficacy of MSC. We explored the molecular mechanism of MSC in the treatment of ALF by detecting liver inflammatory response and hepatocyte death. Results In this study, we found that the therapeutic potential of MSC on ALF is dependent on the secretion of prostaglandin E2 (PGE2), a bioactive lipid. MSC-derived PGE2 inhibited TGF-β-activated kinase 1 (TAK1) signaling and NLRP3 inflammasome activation in liver macrophages to decrease the production of inflammatory cytokines. Meanwhile, macrophages in the liver could be induced to anti-inflammatory (M2) macrophages by MSC-derived PGE2 via STAT6 and mechanistic target of rapamycin (mTOR) signaling, which then promote inflammatory resolution and limit liver injury. Finally, administrating EP4 antagonist significantly ameliorated the therapeutic ability of MSC, which promoted liver inflammation and decreased M2 macrophages. Conclusions Our results indicate that PGE2 might be a novel important mediator of MSC in treating ALF, which is through inhibiting the liver inflammatory response and hepatocyte death.